Applications of MALDI-TOF-MS in structural characterization of synthetic polymers. Issue 7 (6th February 2023) - Sun, A. 'Bin; Li, Siting; Kou, Xinhui
Abstract : MALDI-TOF-MS plays important roles in the characterization of various synthetic polymers, which can provide the molecular weight, repeat unit, end groups, polymerization mechanism and other information on the analyte polymers. Abstract : In recent years, matrix assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) has been utilized to rapidly and precisely characterize the detailed molecular structures of synthetic polymers. This review summarizes recent progress regarding MALDI-TOF-MS for the characterization of synthetic polymers with a focus on specific important experimental aspects including sample preparation, the choice of matrix, the effects of cationizing agents and solvents, data processing and various applications. Finally, the recent trend of MALDI-TOF-MS development is discussed. We hope this review will be instructive for graduate students and junior users who need to use MALDI-TOF-MS as a necessary characterization technique for new synthetic polymers.